Virulence and genetic analysis of Puccinia graminis tritici in the Indian sub-continent from 2016 to 2022 and evaluation of wheat varieties for stem rust resistance - Prasad, Pramod; Thakur, Rajnikant; Bhardwaj, S. C.; Savadi, Siddanna; Gangwar, O. P.; Lata, Charu; Adhikari, Sneha; Kumar, Subodh; Kundu, Sonu; Manjul, A. S.; Prakasha, T. L.; Navathe, Sudhir; et al. (Frontiers in Plant Science, 2023)
Wheat stem rust, caused by Puccinia graminis f. sp. tritici (Pgt), has re-emerged as one of the major concerns for global wheat production since the evolution of Ug99 and other virulent pathotypes of Pgt from East Africa, Europe, Central Asia, and other regions. Host resistance is the most effective, economic, and eco-friendly approach for managing stem rust. Understanding the virulence nature, genetic diversity, origin, distribution, and evolutionary pattern of Pgt pathotypes over time and space is a prerequisite for effectively managing newly emerging Pgt isolates through host resistance. In the present study, we monitored the occurrence of stem rust of wheat in India and neighboring countries from 2016 to 2022, collected 620 single-pustule isolates of Pgt from six states of India and Nepal, and analyzed them on Indian stem rust differentials; and determined their virulence phenotypes & molecular genotypes. Ug99 type of pathotypes did not occur in India. Pathotypes 11 and 40A were most predominant during these years. Virulence phenotyping of these isolates identified fourteen Pgt pathotypes, which were genotyped using 37 Puccinia spp.-specific polymorphic microsatellites, followed by additional phylogenetic analyses using DARwin. These analyses identified three major molecular groups, demonstrating fewer lineages, clonality, and long-distance migration of Pgt isolates in India. Fourteen of the forty recently released Indian wheat varieties exhibited complete resistance to all 23 Pgt pathotypes at the seedling stage. Twelve Sr genes were postulated in thirty-nine varieties based on their seedling response to Pgt pathotypes. The adult plant stem rust response of these varieties was also assessed at five geographically different locations during two crop seasons. The values of slow rusting parameters i.e. coefficient of infection, area under disease progress curve and infection rates indicated slow rusting behavior of several varieties. Six Sr genes (Sr2, Sr57, Sr58, Sr24, Sr31, and Sr38) were identified in 24 wheat varieties using six molecular markers closely linked to these genes. These findings will guide future breeding programs toward more effective management of wheat stem rust.